A Review of the Concept of People's Housing Savings Reviewed from the General Principles of Good Governance - Vega, Ammelya; Agustin , Fadilah; Farid , Mochamad; Permana , Deni Yusup; Daulay , Annisa A. (Journal of Legal and Cultural Analytics, 2025)
Tapera was established to help the people. However, workers consider the 3% funding cut to be detrimental. This can answer the question of how the idea of public housing savings is seen from the principles of good governance. This research aims to increase knowledge about the concept of public housing savings by looking at the general principles of good governance. Doctrinal law research is carried out using a legislative approach. This tapera program is considered non-transparent because it uses unclear terms to explain how funds are used. Workers felt disadvantaged by the deduction of tapera funds, so they filed a material appeal to the constitutional court. The Tapera program was then evaluated because the concept was similar to the three million houses program.